Rational or Emotional? Unraveling the Motivations Behind Online Impulsive Buying - Liesta Verawati (Global Sustainability Research Institute, 2025)
The increasing prevalence of e-commerce and the emergence of live shopping have contributed to the growing consumerist and hedonistic lifestyle among Indonesians. Several factors, such as free shipping, vouchers, promotions, and cashback, drive unplanned purchases. This study aims to investigate how Indonesian consumers engage in impulsive buying from the perspective of hedonic shopping motivation. Additionally, it examines how situational characteristics and hedonic shopping motivations influence impulsive buying behavior. The research focuses on online purchases through e-marketplaces, as online shopping remains highly popular among younger consumers. Data was collected using an electronic questionnaire distributed via Google Forms, with a sample size of 110 respondents selected through purposive sampling. The study employed a quantitative research approach, and data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with SmartPLS version 3 to assess the measurement model and the structural model. The findings reveal that hedonic shopping motivations comprising dimensions of value shopping, relaxation shopping, adventure shopping, and idea shopping have a positive and significant effect on online impulsive buying. However, time availability does not have a moderating effect on the relationship between hedonic shopping motivations and online impulsive buying.